Il circolo vizioso della anaskeué (Quando si confuta una storia, 1) - Luigi Spina (Annali Online dell'Università di Ferrara. Sezione Lettere)
Among the exercices practiced during a course of rhetorical education, the anaskeué (refutation or confutation), consisted in crtiticizing a well known, mythical or factual, narration. In some rhetorical handbooks anaskeué was only a skill to practice other progymnasmata. By analysing the different classifications and descriptions of the anaskeué, with the relating examples, one can recognize in the contemporary arguments of negationism the bad and dangerous side of the anaskeué.